THE THICKNESS OF A THIN FILM SYNTHESIZED FROM LIDAH MERTUA PLANT (SANSEVIERIA TRIFASCIATA) USING A DIP COATING METHOD - Ervina Sandra Dewi; Siti Alaa; Dian Wijaya Kurniawidi; Susi Rahayu (Universitas Mataram, 2019)
A study has been conducted on the characterization of optical properties of thin films from lidah mertua (Sansevieria trifasciata) with dip coating method. The dip coating method was applied with different temperature and different time immersion treatments. The measuring variables in the manufacture of this thin film were tested based on the optical properties of their absorbance value of the extract and the thicknessof thin film. The absorbance spectral of extraction pigments were measured using UV-Vis in the wavelength range 350 nm to 700 nm. The results of the measurements showed that the extract of the S. trifasciata has high absorbance. Beside that, the minimum coating thickness is produced by a concentration of 12.5% with a 5 minute immersion time of 520 nm.